CYTOCHEMISTRY AND ELECTRON MICROSCOPY : The Preservation of Cellular Ultrastructure and Enzymatic Activity by Aldehyde Fixation - Sabatini, David D. (The Rockefeller University Press, 1963)
The aldehydes introduced in this paper and the more appropriate concentrations for their general use as fixatives are: 4 to 6.5 per cent glutaraldehyde, 4 per cent glyoxal, 12.5 per cent hydroxyadipaldehyde, 10 per cent crotonaldehyde, 5 per cent pyruvic aldehyde, 10 per cent acetaldehyde, and 5 per cent methacrolein. These were prepared as cacodylate- or phosphate-buffered solutions (0.1 to 0.2 M, pH 6.5 to 7.6) that, with the exception of glutaraldehyde, contained sucrose (0.22 to 0.55 M). After fixation of from 0.5 hour to 24 hours, the blocks were stored in cold (4°C) buffer (0.1 M) plus sucrose (0.22 M). This material was used for enzyme histochemistry, for electron microscopy (both with and without a second fixation with 1 or 2 per cent osmium tetroxide) after Epon embedding, and for the combination of the two techniques. After fixation in aldehyde, membranous differentiations of the cell were not apparent and the nuclear structure differed from that commonly observed with osmium tetroxide. A postfixation in osmium tetroxide, even after long periods of storage, developed an image that—notable in the case of glutaraldehyde—was largely indistinguishable from that of tissues fixed under optimal conditions with osmium tetroxide alone. Aliesterase, acetylcholinesterase, alkaline phosphatase, acid phosphatase, 5-nucleotidase, adenosine triphosphatase, and DPNH and TPNH diaphorase activities were demonstrable histochemically after most of the fixatives. Cytochrome oxidase, succinic dehydrogenase, and glucose-6-phosphatase were retained after hydroxyaldipaldehyde and, to a lesser extent, after glyoxal fixation. The final product of the activity of several of the above-mentioned enzymes was localized in relation to the fine structure. For this purpose the double fixation procedure was used, selecting in each case the appropriate aldehyde.